The computational aspects of estimating the efficiency of wireless networks' topology - Thike, Aye Min; Lupin, Sergey; Than, Ba Hla; Chakirov, Roustiam (2017 IEEE Conference of Russian Young Researchers in Electrical and Electronic Engineering (EIConRus), 2017)
Wireless Network has become the critical part of the communication infrastructure in our environment. Nowadays, the using of mobile computing devices such as laptops and Wi-Fi enabled phones in the workplace is increasing. The design of wireless networks for enterprise environments remains a challenging task due to the problem of topological design. In this paper, we discuss the computational aspects of the task of calculation the various criteria of efficiency wireless networks' topology. These criteria determine the different characteristics of wireless networks - the access level of populations to network services, the level of the distributed signal and the level of signal accepted in the city. We use brute force algorithm for comparing the different criteria of efficiency the topology of wireless networks. The brute force algorithm has high computational complexity therefore in our experiments we use parallel computing to solve the problem. For illustration the results we use the task of optimization the Wireless network topology for fragment of Myanmar territory.